Superior Enhancement of Cutaneous Microcirculation Due to “Cyclic” Application of a Negative Pressure Wound Therapy Device in Humans – Local and Remote Effects - Sogorski, Alexander; Becker, Amira; Dadras, Mehran; Wallner, Christoph; Wagner, Johannes Maximillian; Glinski, Maxi v; Lehnhardt, Marcus; Behr, Björn (Frontiers in Surgery, 2022)
Despite a common utilization of “Negative Pressure Wound Therapy”-Devices (NPWT) in a wide range of specialties, still some of the techniques’ basic mechanisms of action are on debate. Conflicting results from prior studies demonstrate our lack of understanding how wound-bed perfusion or cutaneous microcirculation is affected by NPWT. We conducted a prospective randomized study, including 45 healthy subjects, to further investigate the acute effects of NPWT on cutaneous microcirculation underneath the applied dressing. Three modes of application: continuous, intermittent, cyclic were tested. Amongst others, measurements of elicited surface pressure and a comprehensive microcirculatory analysis were carried out utilizing an O2C-device. For detection of (systemic) remote effects perfusion changes of the contra-lateral thigh were evaluated. All three tested modes of application led to a significant (p < 0.05) improvement in local tissue perfusion with an increased blood flow of max + 151 % and tissue oxygen saturation of + 28.2 % compared to baseline values. Surface pressure under the dressing significantly increased up to 29.29 mmHg due to activation of the NPWT-device. Continuous, intermittent and cyclic application of negative pressure was accurately sensed by participants resulting in reported pain values that mirrored the different levels of applied suction. Although cyclic application mode showed the most pronounced effects regarding microcirculatory changes, no statistical significance between groups was observed. We could demonstrate a significant improvement of cutaneous microcirculation under an applied NPWT-dressing with favorable effects due to cyclic mode of application. Most likely an increased surface pressure leads to a better venous drainage of the tissue, which was shown to increase arterial inflow with a consecutive improvement of oxygen supply. Further research is warranted to evaluate our findings regarding wound bed perfusion in the clinical field with respect to formation of granulation tissue and wound healing.